Maternal, Decidual, and Neonatal Lymphocyte Composition Is Affected in Pregnant Kidney Transplant Recipients - Feyaerts, Dorien; Gillard, Joshua; van Cranenbroek, Bram; Rigodanzo Marins, Lina; Baghdady, Mariam M. S.; Comitini, Gaia; Lely, A. Titia; van Hamersvelt, Henk W.; van der Heijden, Olivier W. H.; Joosten, Irma; van der Molen, Renate G. (Frontiers in Immunology, 2021)
Pregnancy after renal transplantation is associated with an increased risk of complications. While a delicately balanced uterine immune system is essential for a successful pregnancy, little is known about the uterine immune environment of pregnant kidney transplant recipients. Moreover, children born to kidney transplant recipients are exposed in utero to immunosuppressive drugs, with possible consequences for neonatal outcomes. Here, we defined the effects of kidney transplantation on the immune cell composition during pregnancy with a cohort of kidney transplant recipients as well as healthy controls with uncomplicated pregnancies. Maternal immune cells from peripheral blood were collected during pregnancy as well as from decidua and cord blood obtained after delivery. Multiparameter flow cytometry was used to identify and characterize populations of cells. While systemic immune cell frequencies were altered in kidney transplant patients, immune cell dynamics over the course of pregnancy were largely similar to healthy women. In the decidua of women with a kidney transplant, we observed a decreased frequency of HLA-DR+ Treg, particularly in those treated with tacrolimus versus those that were treated with azathioprine next to tacrolimus, or with azathioprine alone. In addition, both the innate and adaptive neonatal immune system of children born to kidney transplant recipients was significantly altered compared to neonates born from uncomplicated pregnancies. Overall, our findings indicate a significant and distinct impact on the maternal systemic, uterine, and neonatal immune cell composition in pregnant kidney transplant recipients, which could have important consequences for the incidence of pregnancy complications, treatment decisions, and the offspring’s health.